2012
DOI: 10.1590/s1413-70542012000100006
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of tomato strains to the moth Tuta absoluta imparted by allelochemicals and trichome density

Abstract: We examined the resistance of improved tomato strains rich in 2-tridecanone (2-TD), zingiberene (ZGB) and acyl sugars (AA) to the tomato moth, Tuta absoluta. We also studied whether selection for strains with higher densities of glandular trichomes, and thus presumably strains with higher concentrations of 2-tridecanone, was effective in promoting greater resistance to the moth. The TOM-584 and TOM-679 strains were used as susceptible controls, which have normal concentrations of the three allelochemicals. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
55
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 12 publications
10
55
0
3
Order By: Relevance
“…Similar results as indirect selection were found by Oliveira et al (2012), selected genotypes with the highest trichome density and found levels of resistance to the moth Tuta absoluta that were much higher than those exhibited by susceptible controls, and treatment BPX-367D-238-02 was particularly effective. Maluf et al (2007) found similar results of indirect selection for resistance to the red spider mite T. urticae.…”
Section: Resultssupporting
confidence: 78%
“…Similar results as indirect selection were found by Oliveira et al (2012), selected genotypes with the highest trichome density and found levels of resistance to the moth Tuta absoluta that were much higher than those exhibited by susceptible controls, and treatment BPX-367D-238-02 was particularly effective. Maluf et al (2007) found similar results of indirect selection for resistance to the red spider mite T. urticae.…”
Section: Resultssupporting
confidence: 78%
“…Tomato leaf has volatile compounds such as terpenoid that attracts mated females for oviposition. Plant cultivars, rich in 2-tridecane or zingiberene that are chemicals used to give tomato resistance against beet armyworm are not preferred for oviposition by T. absoluta (De Oliveira et al, 2012). However, plants with the absence or less content of terpenes that is herbivores repellent compound are preferable to T. absoluta oviposition (Proffit et al, 2011;Shehata et al, 2016).…”
Section: Host Plant Selection Mechanism and Life Cycle Of T Absolutamentioning
confidence: 99%
“…This includes, cultural control measures (crop rotation, selective removal and destruction of infested plant material) (Korycinska et al, 2009), using natural enemies (parasitoids, predators, entomopathogens and nematodes) (Desneux et al, 2010;Urbaneja et al, 2012), botanicals and production of resistant tomato cultivar varieties (De Oliveira et al, 2012). The integration of these methods with each other and if possible with less environmental hazardous insecticides are important to control T. absoluta without disturbing ecological world.…”
Section: Ipm Strategy and Its Effectivenessmentioning
confidence: 99%
See 2 more Smart Citations